Event Study Analysis of The Lock Down Tourism, Hospitality, Restaurant and Pharmaceuntical Sub-Sector in Indonesia - Putranti (SINTA ID: 6712751), Latifah; Agista Cahya Nirmala (Department of Management, Universitas PGRI Yogyakarta., 2024)
Purpose: This research aims to find out whether there are differences in stockreturns and stock trading volume before and after the announcement of the firstPSBB in Indonesia on March 31, 2020, in the tourism, hotel and restaurant subsector - the pharmaceutical sub-sector listed on the Indonesia Stock Exchange. Methodology: The population in this study were all companies in the tourism,hospitality and restaurant sub-sector - pharmaceutical sub-sector registered onthe IDX in 2020. The samples obtained from predetermined criteria were 14 forthe tourism, hotel and restaurant sub-sector and 9 for the pharmaceutical subsector. This research took place for 27 weeks (6 months) before and 27 weeks (6months) after the PSBB announcement. This research is quantitative researchusing secondary data. The data analysis method used is descriptive analysis,normality test (Kolmogorov Smirnov), and difference test (Wilcoxon Sign RankTest). Findings: The results of the weekly difference test of returns and stock tradingvolume in these two sectors, on average, did not experience significantdifferences